Предмет: Алгебра,
автор: Аноним
ПЛИИИИИИИИЗ ПОМОГИТЕ СРОЧНО
Приложения:
Ответы
Автор ответа:
0
-5(а²-4/5*а-1/5)=-5(а²-2*а*2/5+4/5-4/5-1/5)=-5((а-2/5)²-9/25)=
=-5(а-2/5-3/5)(а-2/5+3/5)=-5(а-1)(а+1/5)=-(а-1)(5а+1)=(1-а)(5а+1) это числитель
(1-5а)(1+5а) знаменатель сократим на (1+5а) получится
(1-а)/(1-5а)
Похожие вопросы
Предмет: Алгебра,
автор: mmaspanoff
Предмет: Математика,
автор: alua07062014
Предмет: Алгебра,
автор: akylai42
Предмет: Биология,
автор: otarov90
Предмет: Биология,
автор: barbusasha